De panfletos eletrônicos a canais efetivos: uma análise dos dispositivos tecnológicos de participação nos websites das Assembleias Legislativas - Melo, Licemar Vieira (Universidade do Vale do Rio dos Sinos, 2023)
This is a qualitative-quantitative research that seeks to understand whether the technological participation devices offered on the websites of the 26 Legislative Assemblies allow citizens to exercise Non-Electoral Democratic Controls over the work of state deputies and, ultimately, about the legislative process itself. In this investigation, channels on legislative portals that allow citizen participation were considered DTPs. The CDNE corresponds to a recent concept discussed by Ernesto Isunza Vera and Adrián Gurza Lavalle (2018) that encompasses contemporary democratic innovations capable of, in a representative system, changing the relationship between the State and social actors (individual and collective), by presupposing a leading role in social participation with the potential to influence the actions of public agents, including political representatives. This investigation included two empirical immersions. In the first, eight technological participation devices announced as being offered on the websites of the Legislative Assemblies were identified, based on pre-established analytical categories: Request for information, Deputies, Commissions, Legislative proposals, Public hearings, Public consultations, Ombudsman and Submission of legislative suggestions. In the second data collection, with an exploratory bias, there were incursions/tests on the devices, to check how they worked and what they allowed the citizen to do. The findings allowed us to conclude that the majority of devices present in the 26 legislative portals analyzed provide citizens with access to information. Despite recognizing the importance of access to information for monitoring the work of deputies in state parliaments, it guarantees the exercise of punctual and weak non-electoral democratic controls. This study indicates that, in order to exercise strong non-electoral democratic controls, it is necessary to move forward in the sense that participation through technological participation devices encompasses, in addition to access to information on the actions of parliamentarians, their accountability and sanctions. This thesis makes contributions: the suggestion to include two new analytical categories of e-participation for analyzing digital democracy initiatives in parliaments; methodological innovations based on two data collections carried out and the pilot project for the production of a booklet, with the provisional title of “Good Practices for the promotion of electronic participation in the Legislative Branch”, to be produced based on the findings in the incursions/ test in technological participation devices, carried out for the production of this thesis, and discussions that 13 we intend to promote with technicians and researchers in the area of electronic parliament in Brazil.
Keywords: Democracia digital; Parlamento eletrônico; Participação eletrônica; Controles democráticos não eleitorais; Digital democracy; Electronic parliament; Electronic participation; Nonelectoral democratic controls; ACCNPQ::Ciências Humanas::Sociologia